100m and 200m short sprints drills - Khmel, M. (The Best of British Track & Field Drills Series, 2009)
Coach Michael Khmel begins this short-sprint presentation with a maximum velocity development segment that is designed to improve quickness for the first 30 meters. He includes quickness drills for knee drive as well as arm quickness. Next, Coach Khmel focuses on build-up drills designed to get the sprinter to a speed that he or she will carry for the duration of the event. Khmel stresses that speed is based upon frequency and length of stride and shares sprinting drills that assist in determining these factors for a sprinter. In his final segment, Khmel shares technical strategies of the block start. His instruction focuses upon the need to individualize the start sharing technical tips along with common errors and corrections that will help you build the ideal start for your sprinters. Throughout each segment, Khmel offers ongoing technical narration with performance tips for short sprint development.